The State's Responsibility in Forest Fires in Indonesia - Muhammad Arifin (Britain International for Academic Research (BIAR) Publisher, 2020)
The problem of forest fires becomes a complex problem and even impacts not only the domestic sphere, but also has an impact on foreign countries (neighbors). This problem arises not only due to natural factors, but also due to human factors. This is an extraordinary crime, which is constitutionally the responsibility of the state. This study aims to analyze how the concept of state responsibility in the issue of forest fires in the case approach and the concept of green constituency. The method used in this research is normative legal research premises library research data collection methods. Which shows that the government in the case of forest fires is constitutionally responsible, because Indonesia adheres to the concept of green constitution which reinforces the ecological position in the development of the nation and state.